THEORETICAL FOUNDATIONS, PRINCIPLES, AND PEDAGOGICAL CONDITIONS FOR DEVELOPING REFLECTIVE THINKING IN STUDENTS BASED ON MODERN PEDAGOGICAL TECHNOLOGIES - Ergasheva Nigora Dilshodjon qizi (The Conference Hub, 2025)
This article analyzes the theoretical foundations of developing reflective thinking in students, its close interrelation with modern pedagogical technologies, the key principles of this process, and the pedagogical conditions necessary for its effective implementation. Reflective thinking plays an essential role in the process of consciously analyzing knowledge, evaluating one’s own activity, and improving it. Modern pedagogical technologies, in turn, serve as powerful tools for effectively organizing this process.
Keywords: Reflective thinking, modern pedagogical technologies, theoretical foundations, principles, pedagogical conditions.